2023
DOI: 10.3390/plants12142660
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination Ecology of the Medicinal Plant Peganum harmala (Zygophyllaceae)

Abstract: Seed germination is a crucial stage in the life cycle of annuals in arid, saline regions and is particularly vulnerable to abiotic stresses. Peganum harmala, a valuable medicinal plant, has limited research on its seed germination response to different environmental stresses in the arid, saline regions of Central Asia. To investigate this, we studied the effects of various temperature regimes (ranging from 20/5 to 35/20 °C), light exposure (12 hours light/12 hours dark and continuous dark), seven levels of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In this case report, it was indicated that three Syrian rue seeds were consumed. However, considering the tiny weight ( Li et al, 2023 ) and the average content of alkaloids in these seeds ( Herraiz et al, 2010 ), the estimated total harmaline and harmine content would be only approximately 0.26 mg and 0.34 mg, respectively. The combined amount is at least 50 times less than the same alkaloid levels typically used in a standard ayahuasca brew for MAO inhibition ( D. J. McKenna et al, 1984 ; Rivier and Lindgren, 1972 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case report, it was indicated that three Syrian rue seeds were consumed. However, considering the tiny weight ( Li et al, 2023 ) and the average content of alkaloids in these seeds ( Herraiz et al, 2010 ), the estimated total harmaline and harmine content would be only approximately 0.26 mg and 0.34 mg, respectively. The combined amount is at least 50 times less than the same alkaloid levels typically used in a standard ayahuasca brew for MAO inhibition ( D. J. McKenna et al, 1984 ; Rivier and Lindgren, 1972 ).…”
Section: Discussionmentioning
confidence: 99%